Між діаспорою та Батьківщиною: зміни у статусі єврейських жінок із Захо (Курдистан) за їхніми особистими оповідями - Гавіш, Х. (Народна творчість та етнографія, 2008)
The Jewish community of Zakho served as a spiritual and religious center in the northern mountain region of Kurdistan. The family structure was patriarchal; the women were housekeepers and were responsible for the education of the girls and the male children. Changes in the status of women occurred when they fully identified with collective communal values, such as religious attachment to Eretz Israel, and to Jerusalem, in particular. Thus, the change in status of Kurdistani Jewish women began prior to their immigration, while in the State of Israel they gradually consolidated their status on an equal standing with men.